Study of Disordered Mesoporous Silica Regarding Intrinsic Compound Affinity to the Carrier and Drug-Accessible Surface Area - Niederquell, Andreas; Vraníková, Barbora; Kuentz, Martin (Molecular pharmaceutics, 2023)
There is increasing research interest in using mesoporous silica for the delivery of poorly water-soluble drugs that are stabilized in a noncrystalline form. Most research has been done on ordered silica, whereas far fewer studies have been published on using nonordered mesoporous silica, and little is known about intrinsic drug affinity to the silica surface. The present mechanistic study uses inverse gas chromatography (IGC) to analyze the surface energies of three different commercially available disordered mesoporous silica grades in the gas phase. Using the more drug-like probe molecule octane instead of nitrogen, the concept of a "drug-accessible surface area" is hereby introduced, and the effect on drug monolayer capacity is addressed. In addition, enthalpic interactions of molecules with the silica surface were calculated based on molecular mechanics, and entropic energy contributions of volatiles were estimated considering molecular flexibility. These free energy contributions were used in a regression model, giving a successful comparison with experimental desorption energies from IGC. It is proposed that a simplified model for drugs based only on the enthalpic interactions can provide an affinity ranking to the silica surface. Following this preformulation research on mesoporous silica, future studies may harness the presented concepts to guide formulation scientists.
Keywords: drug-accessible surface area; Pharmaceutical Preparations; oxid křemičitý; léčivé přípravky; Solubility; poréznost; Silicon Dioxide; Water; drug−silica interaction prediction; mesoporous silica carrier; rozpustnost; modeling-based prediction; Porosity; inverse gas chromatography; monolayer capacity; voda